2021
DOI: 10.3389/fonc.2021.683656
|View full text |Cite
|
Sign up to set email alerts
|

“High-Risk Breast Cancer Screening in BRCA1/2 Carriers Leads to Early Detection and Improved Survival After a Breast Cancer Diagnosis”

Abstract: BackgroundGermline BRCA1/2 pathogenic variant (PV) carriers have high lifetime risk of developing breast cancer and therefore subjected to intense lifetime screening. However, solid data on the effectiveness of high-risk screening of the BRCA1/2 carrier population is limited.Patients and MethodsRetrospectively, we analyzed 346 women diagnosed with breast tumors. Patients were divided according to the timing of BRCA1/2 PVrecognition, before (BRCA-preDx awareness, N = 62) or after (BRCA-postDx awareness group, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…6 For those who forgo mastectomy, intensive follow-up with annual MRI alternating with mammography and breast ultrasound allows early detection and curative treatment of BC 37 and may improve survival. 38 Nevertheless, nonsurgical prevention seems highly desirable and could alleviate morbidity and suffering.…”
Section: Contralateral Breast Cancermentioning
confidence: 99%
“…6 For those who forgo mastectomy, intensive follow-up with annual MRI alternating with mammography and breast ultrasound allows early detection and curative treatment of BC 37 and may improve survival. 38 Nevertheless, nonsurgical prevention seems highly desirable and could alleviate morbidity and suffering.…”
Section: Contralateral Breast Cancermentioning
confidence: 99%
“…The role of BRCA1 & BRCA2 gene as important risk factors for the development of breast cancer is well-established; however, this association has been mostly directed to invasive breast cancers 65 . Nevertheless, it appears that with increased emphasis on early breast cancer screening and the recommendation for the use of MRI in carriers of breast cancer genes, carcinoma in situ lesions are now being more frequently identified 66 . It appears that BRCA1-related DCIS is diagnosed earlier, more likely to be estrogen receptor-negative and of higher grade than BRCA2-related DCIS.…”
Section: The Association Of Breast Cancer Genes and Low-grade Dcismentioning
confidence: 99%
“…65 Nevertheless, it appears that with increased emphasis on early breast cancer screening and the recommendation for the use of MRI in carriers of breast cancer genes, carcinoma in situ lesions are now being more frequently identified. 66 It appears that BRCA1-related DCIS is diagnosed earlier, more likely to be estrogen receptor-negative and of higher grade than BRCA2-related DCIS. More studies are required to better identify the relationship between breast cancer genes and low-grade DCIS.…”
Section: The Association Of Breast Cancer Genes and Low-grade Dcismentioning
confidence: 99%
“…The current screening guidelines for female BRCA PVs carriers, including bi-annual breast imaging [ 7 ], have been shown to increase the rate of early diagnosis with more in-situ pathology, smaller tumors, and less axillary involvement compared with carriers who do not adhere to the suggested surveillance scheme [ 7 , 8 , 9 , 10 ]. MRI is considered the most sensitive modality for BC detection in BRCA PV carriers, with sensitivity rates of up to 96% [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current screening guidelines for female BRCA PVs carriers, including bi-annual breast imaging [ 7 ], have been shown to increase the rate of early diagnosis with more in-situ pathology, smaller tumors, and less axillary involvement compared with carriers who do not adhere to the suggested surveillance scheme [ 7 , 8 , 9 , 10 ]. MRI is considered the most sensitive modality for BC detection in BRCA PV carriers, with sensitivity rates of up to 96% [ 10 , 11 , 12 , 13 ]. Yet several studies have shown that, in retrospective analyses, in a significant number of MRI detected BCs (50–74%), localized radiological abnormalities were present in the prior MRI, which was performed approximately one year before actual BC diagnosis [ 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%